2013
DOI: 10.3846/13923730.2012.760479
|View full text |Cite
|
Sign up to set email alerts
|

Change in Uk Construction: Moving Toward Supply Chain Collaboration

Abstract: The traditional adversarial relationship in the construction industry has been criticized by a larger number of researchers and practitioners. Following the success of the supply chain collaboration in other industry sectors, such as manufacturing, supply chain relationships in UK construction have been increasingly changing from the traditional adversarial to the collaborative, which is supported by a series of government reports for the industry reform. However, few empirical studies have been conducted to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 36 publications
0
36
0
1
Order By: Relevance
“…Fearne and Fowler, 2006;Fernie and Tennant, 2013;Meng, 2013;Vrijhoef and Koskela, 2000), and it will be analysed based on a literature review. The main focus of the review is on TPL, in particular on driving forces and concerns for implementing TPL.…”
Section: Introductionmentioning
confidence: 99%
“…Fearne and Fowler, 2006;Fernie and Tennant, 2013;Meng, 2013;Vrijhoef and Koskela, 2000), and it will be analysed based on a literature review. The main focus of the review is on TPL, in particular on driving forces and concerns for implementing TPL.…”
Section: Introductionmentioning
confidence: 99%
“…From the large main contractors' perspective, it has been more important to secure contracts from their customers, i.e. the clients, than focusing on the extended supply chain (Meng, 2013). A consequence is that it has been hard for subcontractors and suppliers to be included in the partnering agreements.…”
Section: Trustmentioning
confidence: 99%
“…The contracts between main contractors and subcontractors have been more like traditional adversarial agreements. Because of the fragmentation in the construction industry, with competition between many small construction contractors, the subcontractors have been afraid to state demands with the risk of losing contracts (Meng, 2013;Dainty et al, 2001a;Dainty et al, 2001b). Although some suppliers have initiated partnering agreements of their own (Wolstenholme, 2009), many suppliers are skeptical about partnering, viewing it as a way to push costs upstream in the supply chain Akintoye et al, 2000).…”
Section: Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Monczka et al (2011) found that nearly 50% of the quality problems result from working with wrong suppliers and poor management of the supply chain. Meng (2013) claims that the traditional adversarial supply chain relationship brings about various problems, e.g., claims, conflicts, disputes, low productivity, delays, cost overruns, quality defects, and customer dissatisfaction. Verma and Pullman (1998) found that even though managers claim that quality is the most important criterion in selecting a supplier, in real life, they predominantly select suppliers based on two criteria, namely product price and delivery performance.…”
Section: Introductionmentioning
confidence: 99%